Does the marketisation of pensions lead to individualisation? An examination of family-related pension entitlements. (1st October 2019) - Frericks, Patricia; Höppner, Julia
Abstract : Countries around the world have undertaken pension reforms and introduced market-based schemes to replace parts of existing public schemes. Previous research has shown how these reforms are often driven by a commitment to individualisation, and accompanied by rhetoric that encourages 'self-responsibility'. To date, however, no research has examined the effects of this shift on family-related pension entitlements. In response, this article provides a critical analysis of whether family-related pension rights have, indeed, decreased in the course of marketisation. Through a systematic comparison of Austria and Germany, we show that this is not the case: family-related rights have been included in newly introduced market-based schemes; and pension reforms did not lead to individualisation in either existing public or market-based schemes. As a result, we argue that reform trajectories are path-dependent and contextual; and that future studies should focus on non-individual entitlements when assessing welfare marketisation in general and pension reforms in particular.